2021
DOI: 10.1002/berj.3729
|View full text |Cite
|
Sign up to set email alerts
|

Grade retention and academic self‐concept: A multilevel analysis of the effects of schools’ retention composition

Abstract: Previous studies on the impact of grade retention on academic self-concept suffer from inconclusive findings. There is no consensus if retention yields long-term benefits that could offset its opportunity costs and, if so, under what conditions. Therefore, this article examines whether grade retention decreases academic self-concept and whether this relationship is mediated by sense of belonging. Moreover, we aim to contextualise retention research by accounting for schools' retention composition. Based on ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 48 publications
(149 reference statements)
2
26
1
3
Order By: Relevance
“…Such findings suggest that the remediation measure had a positive effect on achievement motivation, at least in the dimension of expectancies for success. This implies that it may have fewer negative consequences than grade retention, a measure that is known to lead students to develop doubts about their capacities (Kretschmann et al, 2019; Martin, 2009, 2011; Peixoto et al, 2016; Robles‐Piña, 2011; Rosário et al, 2013; Van Canegem et al, 2021), and to evaluate learning (Martin, 2009; Peixoto et al, 2016; Rosário et al, 2013). The remediation measures in this study did not reveal such negative effects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such findings suggest that the remediation measure had a positive effect on achievement motivation, at least in the dimension of expectancies for success. This implies that it may have fewer negative consequences than grade retention, a measure that is known to lead students to develop doubts about their capacities (Kretschmann et al, 2019; Martin, 2009, 2011; Peixoto et al, 2016; Robles‐Piña, 2011; Rosário et al, 2013; Van Canegem et al, 2021), and to evaluate learning (Martin, 2009; Peixoto et al, 2016; Rosário et al, 2013). The remediation measures in this study did not reveal such negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, these potential advantages are contested. Most studies on the effects of grade retention indicate that the practice does not have a clear positive effect on students' learning acquisition (Froiland & Davison, 2014; Klapproth et al, 2016; Mariano et al, 2018) and that it can have harmful effects on students' perceptions of their capacities (Kretschmann et al, 2019; Martin, 2009, 2011; Peixoto et al, 2016; Robles‐Piña, 2011; Van Canegem et al, 2021) as well as the value they place on learning (Kretschmann et al, 2019; Peixoto et al, 2016), which are considered to be important motivational resources.…”
Section: Statement Of Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have found that ASC forms gradually in the first years of school [13], tending to decrease among students in early adolescence [14], and reaching its lowest point in mid-adolescence [15]. However, there is some controversy, since other authors state that ASC is formed at primary school age and reaches its maximum value in secondary school [16], and that it also tends to rise according to the increase in the students' academic performance [10,17], which may be the cause and effect of that performance [18]. Furthermore, several studies have demonstrated that ASC may also be influenced by variables of context, well-being, and the gender of the student [13,14,19].…”
Section: Introductionmentioning
confidence: 99%